CONCEPTUAL MODELS FOR ASSESSING ADVERSARIAL BUSINESS RELATIONSHIP AND IMPROVEMENT OF ENGINEERING AND DESIGN SERVICE DELIVERY (EDSD) IN GHANA - N.K Orgen; D.K Ahadzie; J Ayarkwa; E Badu (Journal of Construction Project Management and Innovation)
Cordial, harmonious business relationship and collaborative business culture that are essential tools for improvement of construction supply chains and networks seem to have eluded Engineering and Design Service Delivery (EDSD) activities despite several years of useful interventions. The aim of this paper was to develop models: to show current EDSD business relationship problems with the view of improving the EDSD activities. The modeling development followed action oriented system theory, system thinking and rethinking. The way of dealing with construction issues in the traditional procurement system in Ghana have been revealed to be adversarial. These offered specific background to demonstrate why the action oriented system theory; system thinking and rethinking were useful in Supply Chain Relationship Management (SCRM) improvement modeling. Further, SCRM improvement modeling is to provide indicative illustration model to overcome the business relationship problems, which have impeded the improvement and continuous improvement of EDSD activities in the past. The desk based search of literature as well helped to develop the models through induction and deduction inferences. These processes were robust attempts pursued based on action oriented system theory, system thinking and rethinking, and relevant literature concepts. Also two separate models for the improvement of the EDSD activities were developed, using performance feedbacks, traditional non adversarial methods/review and innovative information exchange among EDSD practitioners and between them and contractors. One model produced three-stage improvement approach and the other comprising five maturity categorization regions for determination of nine levels of EDSD improvement assessment and continuous improvement in current procurement practice in Ghana.